1979
DOI: 10.1139/b79-206
|View full text |Cite
|
Sign up to set email alerts
|

Growth response of inoculated peas (Pisum sativum) to combined nitrogen

Abstract: Pea plants (Pisum sativum L. cv. Trapper) were inoculated and grown in controlled-environment chambers at two irradiance levels. Shoot and root dry weights and nitrogen contents, total leaf and stipule areas, and rates of C2H2 reduction were determined during growth in different treatments of NH4NO3 addition. Although overall growth increased with irradiance, the growth responses to combined nitrogen addition were similar at both light levels. Two phases of early vegetative growth were identified by their diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
26
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 0 publications
5
26
0
Order By: Relevance
“…Acetylene-reduction though young legumes use large amounts of carbohydrate to rs indicated that root nodules were functioning by 16 days construct root nodules (7) and nodulated soybean root systems respire more CO2 than N03 -dependent root systems (13), raising CO2 from 320 to 1,000 ,ul C02/L had no significant effect on dry Kjeldahl N content by 100 and 168%, respectively, in 22-day-old seedlings (Tables I and II). Such results are consistent with other reports of combined N effects on dry matter accumulation by legumes (6,9), but a direct comparison between relative C and N 10 .…”
Section: Growth Conditionssupporting
confidence: 93%
See 1 more Smart Citation
“…Acetylene-reduction though young legumes use large amounts of carbohydrate to rs indicated that root nodules were functioning by 16 days construct root nodules (7) and nodulated soybean root systems respire more CO2 than N03 -dependent root systems (13), raising CO2 from 320 to 1,000 ,ul C02/L had no significant effect on dry Kjeldahl N content by 100 and 168%, respectively, in 22-day-old seedlings (Tables I and II). Such results are consistent with other reports of combined N effects on dry matter accumulation by legumes (6,9), but a direct comparison between relative C and N 10 .…”
Section: Growth Conditionssupporting
confidence: 93%
“…Photosynthesis in nonlegumes depends on adequate N nutrition from soil reserves (11), but the question of whether symbiotically grown legumes are C-or N-limited is analytically complex (12 term increases in CO2 concentrations around mature legumes promoted plant growth and N2 fixation (8,15). Other workers using seedling material have emphasized that the availability of soil N during the period of root nodule formation limits dry matter accumulation (6,9). The latter point is explained by the fact that the rate of apparent photosynthesis, measured by CO2 exchange, is N-limited during that period (14).…”
mentioning
confidence: 99%
“…This is of special interest in organic systems where soil mineral nitrogen can be a limiting factor while cropping legumes as sole crops can be considered as an inefficient way for utilizing the soil N sources, since the legumes can cover major part of their N requirements by N 2 -fixation. Nevertheless, formation of nodules and their activity in legumes takes place gradually (Tricot et al 1997;Voisin et al 2002) and then legumes depend on soil mineral N and seed N reserves during early growth (Mahon and Child 1979). Thus, at the beginning of growth, the intercropped cereals and legumes components compete for soil mineral nitrogen via root absorption.…”
Section: Partial Conclusion From "Section 2"mentioning
confidence: 99%
“…However, small "starter" doses of fertilizer N have sometimes proved beneficial to plant development and subsequent nodulation and N 2 fixation (Mahon and Child 1979), especially when initial nodulation is restricted or delayed. It has been argued that due to the lag period between Rhizobium root colonization and the onset of nodule functioning, the young legume plants require adequate N from external sources in order to achieve proper vegetative growth and establishment of the N-fixing symbiosis.…”
mentioning
confidence: 99%